TINJAUAN FLUKS CAHAYA, SUHU WARNA, TOTAL HARMONIC DISTORTION, FAKTOR DAYA LAMPU PIJAR, LAMPU HEMAT ENERGI DAN LIGHT EMITTING DIODE - Mulya Haryanto; Eva Magdalena Silalahi; Bambang Widodo; Robinson Purba; Judo Ignatius Nempung (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2020)
Requirements of energy in nowadays are directly proportional with human activities which use a lot of energy, especially for electrical energy, therefore, it is necessary to take energy saving measures such as lighting that use electronic devices with energy efficient. The latest lighting technology is used saving energy lamp (LHE) and light emitting diode (LED) which are designed to replace that use of incandescent lamps. The purpose of this research was to compare lamp based on light flux, colour temperature total harmonic distortion (THD) and power factor. The standard used for luminous lighting flux, the colour temperature standard of SNI 03-6575-2001 and THD using reference IEEE 519-2014.From the study has been done is obtained that level of lighting flux produced by LED type is bigger for twice than LHE type. The best colour temperature is LED with ratio value of 875oK/W. THD current for LHE and LED does not comply the standard, therefore THD current is smaller 4% - 7,3% from LED. The power’s factor produced by LHE and LED is 0.5 to 0.6.